192 MODULATION OF AUTOIMMUNE ARTHRITIS BY A GLYCOSYLATED ANALOG PEPTIDE OF TYPE II COLLAGEN. Issue 1 (1st January 2007) - Myers, L. K.; Tang, B.; Stuart, J. M.; Kang, A. H.
Abstract : Susceptibility to rheumatoid arthritis (RA) is strongly associated with the expression of specific HLA class II alleles, especially HLA-DRB1*0101 (DR1) and DRB1*0401 (DR4). Since HLA class II molecules are known to regulate immunity, it is likely that RA susceptibility is related to an immune reaction. We have focused on type II collagen (CII) as a candidate autoantigen since it is the predominant protein of articular cartilage, and autoimmunity to CII is commonly detected in patients with RA. The immunodominant peptide, recognized by T cells from DR1 transgenic mice, was identified as CII(260-267). Moreover, an analog peptide CII (256-276, N 263, D 266 ) with two critical substitutions was developed that can ameliorate disease when administered after the onset of collagen-induced arthritis (CIA). A recent mass spectroscopic analysis of enzymatic cleavage products of CII indicated that the lysine residue at 264 is partially hydroxylated and also glycosylated. To directly investigate the role of hydroxylysine glycosides, we, in collaboration with Dr. Gregg Fields, synthesized an analog peptide, CII (256-276, L 264 gal, N 263, D 266 ), containing an hydroxylysine galactoside at residue 264. When mice are treated with this peptide, we show clearly an enhanced potency of glycosylated analogs in modulating the arthritis severity in DR 1 Tg mice. This modulation is associated with an overall increase in the IL-4 response to CII. There is also a decrease in the IGg2a antibody subclass response to collagen, together with an increase in the IGg1 response. Data supporting these conclusions will be presented.